Upaya Rri Padang Dalam Meningkatkan Pendengar Muda Melalui Pemanfaatan Media Sosial - Yosdi, Fathurrahman; ., Defhany (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Radio is a mass media that is closely related to the needs of society that can provide various kinds of information, entertainment, and education. The presence of the internet has shifted people's behavior patterns that are more following the development of internet technology, including RRI Padang. RRI Padang strives to improve the quality of broadcast programs in order to attract young listeners, especially on social media. The background of this study aims to find out how RRI Padang's efforts are made in increasing young listeners through the use of social media. This research using qualitative-inductive research is a research method that starts with collecting concrete data and then developing patterns, themes, or general theories from the data. This method of radio with a focus on attracting the younger generation can involve several approaches oriented towards a deep understanding of the preferences, needs, and expectations of young listeners. This research is with data collection techniques in the form of interviews, observations, documentation, and document studies. The result of this study is the success of RRI Padang's efforts in increasing young listeners through the use of social media